The effect of formative assessment in Brazilian university physics courses - Cruz,Émerson (2011)
Most postsecondary physics courses in Brazil offer no meaningful formative assessment opportunities. We implemented online homework with immediate feedback in two courses, one with traditional learners at a public university, and one with non-traditional learners at a private university. In addition, at the public university, clickers were used in lecture. While surveys showed broad acceptance of these techniques by the students and the belief that they helped in learning, grades did not significantly improve - instead, we observed a narrowing of the grade distribution toward mid-range grades at the public university, and no difference at the private university. Our study also identifies a number of logistical and organizational hurdles that need to be overcome before a hopefully more successful implementation of these techniques should be attempted.